Inhaled Nitric Oxide Use in Preterm Infants in California Neonatal Intensive Care Units - Handley, Sara C. (J Perinatol, 2016)
OBJECTIVE: To describe inhaled nitric oxide (iNO) exposure in preterm infants and variation in Neonatal Intensive Care Unit (NICU) use. STUDY DESIGN: This was a retrospective cohort study of infants, 22–33+6/7 weeks gestational age (GA), during 2005–2013. Analyses were stratified by GA and included population characteristics, iNO use over time and hospital variation. RESULT: Of 65 824 infants, 1 718 (2.61%) received iNO. Infants, 22–24+6/7 weeks GA, had the highest incidence of iNO exposure (6.54%). Community NICUs (n = 77, median hospital use rate 0.7%) used less iNO than regional NICUs (n = 23, median hospital use rate 5.8%). In 22–24+6/7 week GA infants the median rate in regional centers was 10.6% (hospital IQR 3.8%–22.6%). CONCLUSION: iNO exposure varied with GA and hospital level, with the most use in extremely premature infants and regional centers. Variation reflects a lack of consensus regarding the appropriate use of iNO for preterm infants.